Accelerating Cell Migration along Radially Aligned Nanofibers through the Addition of Electrosprayed Nanoparticles in a Radial Density Gradient. (26th February 2022) - Xue, Jiajia; Wu, Tong; Qiu, Jichuan; Xia, Younan
Abstract: Scaffolds capable of promoting cell migration from the periphery toward the center along with the radial direction hold promises for tissue regeneration. Here a simple and general method is reported based on masked electrospray for the fabrication of such scaffolds by depositing collagen nanoparticles on radially aligned nanofibers in a radial density gradient. Placed between the metallic needle and the collector, an aperture with tunable opening sizes serves as the mask. By increasing the size of the opening at a fixed speed, the electrosprayed particles take a radial density gradient that decreases from the center to the periphery. When deposited on a glass slide, the radial density gradient of collagen nanoparticles promotes the migration of fibroblasts from the periphery toward the center. By replacing the glass slide with a scaffold comprised of radially aligned nanofibers, a synergetic effect arises to further accelerate cell migration along the radial direction. The synergistic effect can be attributed to a unique combination of the topographic cue arising from the aligned nanofibers and the haptotactic cue enabled by the graded nanoparticles. This study demonstrates a method to maximize cell migration from the periphery toward the center through a combination of topographic and haptotactic cues. Abstract : Two is better than one: Collagen nanoparticles are fabricated in a radial density gradient by masked electrospray with a tunable aperture. When deposited on a scaffold of radially aligned nanofibers, cell migration is accelerated due to the synergy between the topographic cue arising from the aligned nanofibers and the haptotactic cue enabled by the gradient of nanoparticles.